INCREASING THE EFFICIENCY OF MANAGING ITS OWN CAPITAL ENTERPRISE - Hnyp, Nataliya; Yatsyna, Konstantyn (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2021)
The creation and normal functioning of enterprises of any form of ownership is impossible without the formation of sufficient volume of equity. Equity is one of the main indicators during the assessment of creditworthiness, as well as the level of financial security of the enterprise. Factors of internal and external environment are affected by its capital management. The factors of the internal environment reflect the impact of the financial condition and financial results of economic activity on the effectiveness of managing its own capital of the enterprise, they include: payables and receivables; revenue from sales of products; profit; fixed assets and current liabilities. Factors of the external environment, which are determined by the influence of the environment on the efficiency of managing its own capital of the enterprise and characterize the conditions in which the enterprise operates, in particular: inflation rate (consumer price index); Level of registered unemployment; the growth rate of gross domestic product of Ukraine; the growth rate of gross domestic product of Ukraine; The magnitude of the main means of Ukraine. To increase the efficiency of managing its own capital, the enterprise proposes a methodical approach that differs from the existing use of two groups of indicators: absolute and relative. This will contribute to a more in-depth assessment of the influence of internal and external environments on the efficiency of managing its own capital of the enterprise, and will allow adapting the enterprise to crisis situations. The management of own capital is the main component of the financial support of the enterprise. Sustainable financial condition, effective management of its own capital positively affects the implementation of production plans and ensuring the needs of production with the necessary resources (financial, material, labor, informational).